Innovation and the economic downturn: Insights from Portuguese firms - Pinto, Hugo (2018)
Recent research has found evidence of a variety of business profiles regarding innovation during the economic downturn. Several studies reported that firms were reducing or abandoning innovation activities and dropping related expenses while other authors have found that some firms are exploring the economic turbulence as an opportunity for creative destruction and to gain competitive advantage. This article explores the data collected from the last waves of CIS (Community Innovation Survey) in Portugal (2006-2008-2010-2012) to understand the changes in the determinants of the development of innovation activities, product and process innovation, before, during and in the peak of the crisis. The empirical study presents limited dependent variable models to analyse the relevance of structural factors, absorptive capacity and strategic variables in the different periods. The article concludes with implications for the behaviour of firms and innovation resilience.